Caesarean myomectomy - a safe procedure: A retrospective case controlled study - Owolabi, Alexander T; Kuti, Oluwafemi; Loto, Olabisi M; Makinde, Oluwafemiwa N; Adeyemi, Adebanjo B (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Objective(s): The aim of the study is to determine whether myomectomy at the time of caesarean section leads to increase incidence of intrapartum and postpartum complications. Methods: Fourteen women, with uterine fibroids in pregnancy who were treated by caesarean myomectomy between January 2001 and June 2007, were compared retrospectively with fourteen women, without uterine fibroids who had routine caesarean section during the same period. Myomectomy for all types of myoma was performed at caesarean section after the delivery of the baby. Haemorrhage was controlled with the use of Foleys catheter tourniquet and high dose oxytocin infusion. The cases and control were analysed for age of the patient, parity, pre and post-operative haematocrit levels, duration of operation, blood loss, blood transfusions, and incidence of postpartum fever. Results: Caesarean myomectomy resulted in the mean blood loss of 589 ml (range 300-1300 ml) compared with 518 ml (range 350-850 ml) in the control group (p=0.376). The mean duration of operation was longer in the cases of caesarean myomectomy (66.8 mins) than those of the controls (56.4 mins). There were no significant differences between the two groups in the incidence of intraoperative haemorrhage, the need for blood transfusion, post partum fever, and length of hospital stay. Conclusions: This study shows that myomectomy during caesarean section is a safe procedure in experienced hands and is not as dangerous as generations of obstetricians have been trained to believe. Further research is necessary to establish the cost effectiveness of the procedure. Key words: myomectomy, cesarean section, hemorrhage doi:10.3126/njog.v2i2.1457 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 59 - 62